(untitled) (Journal of Contemporary Philology, 2020)
Over the last decades, the margins of manuscripts and early printed books have attracted as much scholarly attention as the primary texts they surround. As a result, the term “paratext” has begun to appear regularly in scholarly debates about premodern verbal or pictorial material found in the marginal white space. One of the main assumptions of Gérard Genette’s theoretical framework is that paratexts – broadly defined as the ‘undefined zone’ surrounding the primary text and mediating between the text, the author and the reader – can add to our understanding of the text. This paper explores whether Genette’s distinction between text and paratext is useful when we attempt to conceptualise early modern South Slavic marginalia. Focusing on an inscription that records an outbreak of plague in the village of Zrze, in 1538, this paper demonstrates that seeing these scattered inscriptions in less dichotomous terms opens the space for understanding the various roles these enigmatic fragments played in the imagination of the early modern South Slavs.